Memory and identity : conversations at the dawn of a millennium - John Paul II, Pope, 1920-2005. (New York : Rizzoli, 2005)
"In this volume, Pope John Paul II speaks for the first time on global politics. He discusses his views on freedom and democracy and speaks about the twentieth-century totalitarian ideologies of communism and nazism. Making an emphatic appeal for mankind to regard freedom "not only as a gift but a task" to be used for the common good, he calls for a dialogue between all the world's civilizations and religions. This work is a unique reflection on human life, and will be admired by thinkers of all religions and nationalities."--BOOK JACKET.
1. Mysterium Iniquitatis : the coexistence of good and evil -- 2. Ideologies of evil -- 3. The limit imposed upon evil in European history -- 4. Redemption as the divine limit imposed upon evil -- 5. The mystery of redemption -- 6. Redemption : victory given as a task to man -- 7. Toward a just use of freedom -- 8. Freedom is for love -- 9. The lessons of recent history -- 10. The mystery of mercy -- 11. On the concept of Patria (native land) -- 12. Patriotism -- 13. The concept of nation -- 14. History -- 15. Nation and culture -- 16. Europe as "native land" -- 17. The evangelization of Central and Eastern Europe -- 18. The positive fruits of the Enlightenment -- 19. The mission of the church -- 20. The relationship between church and state -- 21. Europe in the context of other continents -- 22. Modern democracy -- 23. Back to Europe? -- 24. The maternal memory of the church -- 25. The vertical dimension of European history -- 26. "Someone must have guided that bullet"
Includes bibliographical references.
Keywords: Religion and politics; Liberty; Democracy